Select barriers to harm-reduction services for IDUs in eastern Europe - Curth, Nadja Kehler; Hansson, Liv Nanna; Storm, Frederikke; Lazarus, Jeffrey V (Central European Journal of Public Health, 2009)
Background: In eastern Europe, the high prevalence rates of HIV and the hepatitis C virus (HCV) are concentrated among injecting drug users (IDUs). Harm reduction programmes such as needle and syringe programmes and opioid substitution therapy (OST) have been shown to be effective in preventing these infections. However, structural barriers can limit their effectiveness by hindering access. Methods: Through use of a semi-structured online survey sent to 65 professionals in the region, this study explores the prevalences of age restrictions, user fees or a lack of confidentiality for these programmes as well as HIV/HCV testing programmes. Results: Twenty respondents reported that age restrictions were not widespread in the 11 reporting countries, apart from for OST. User fees were found to be very common in HCV testing and varied for other services. It was stated to be common to inform parents of young IDUs who receive HIV services, but not to inform public authorities when IDUs enter harm reduction programmes. Conclusion: Where access to services is limited or confidentiality is compromised, as reported in this pilot study, it is crucial that health-care guidelines and national legislation are reformed to ensure access to these evidence-based interventions.
Keywords: Europe, Eastern; hepatitida C; střední Asie; internet; HIV Infections; pilotní projekty; intravenózní abúzus drog; methadon; zdravotní politika; poruchy spojené s užíváním psychoaktivních látek; Substance Abuse, Intravenous; průzkumy a dotazníky; Internet; HIV infekce; programy výměny jehel a stříkaček; Methadone; lidé; Humans; Hepatitis C; Preventive Medicine; východní Evropa; Asia, Central; společné užívání jehel; Needle Sharing; Needle-Exchange Programs; Pilot Projects; Surveys and Questionnaires; preventivní lékařství; Health Policy; Substance-Related Disorders